PEMETAAN KUALITAS AIR SUNGAI DI KAWASAN INDUSTRI NGINGAS SIDOARJO DIJINJAU DARI PARAMETER BOD DAN TSS TAHUN 2021 - Fauzi Udianto; Ferry Kriswandana; Rachmaniyah . (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Surabaya, 2022)
Rivers are one of the environmental components that have important functions for human life, including to support environmental balance as a result of increased development activities in various fields. River pollution occurs because of domestic and non-domestic waste. River pollution that occurs in the ngingas river causes a pungent and colorful odor that affects the biota and quality of river water. The purpose of this study was to measure and map river water quality in terms of TSS and BOD parameters. The research is descriptive in nature with the independent variable being effluent along the river and the dependent variable being the levels of TSS and BOD in the ngingas river. The sampling technique used the grab sampling method and composite sampling was carried out by taking 4 points as far as 2 km from the Ngingas River flow. Data analysis was done by descriptive method of BOD and TSS levels as a result of the effluent at the 4 specified points. The results of the measurement of 4 sampling points at the Ngingas River showed BOD and TSS results of 151.5 mg/L and 103 mg/L in the first 1 km caused by domestic waste originating from settlements with the criteria of the waste being slightly foamy, and smelling good. While in the second 1 km the results of TSS and BOD are 814.2 mg/L and 73.8 mg/L, the measurement results can be caused by many factors, namely household activities or industrial activities, with the criteria that the waste is sometimes foamy. , slightly black, cloudy and smelly. Suggestions for other researchers are efforts to reduce TSS and BOD levels that meet the requirements and it is hoped that every industrial owner has a sewage treatment plant.